Disability and eLearning: Opportunities and Barriers - Kent, Mike (Disability Studies Quarterly, 2015)
This paper explores the current rising rates of online learning in higher education. It examines how disability is activated differently online and the impact of this on learning and teaching through the internet and the accessibility of two of the most popular learning management systems, Blackboard and Moodle, and the different approaches, benefits and problems associated with each system. It then explores the eLearning environment beyond the structure of a LMS to a broader digital campus that includes social networks, video hosting sites and micro blogging, where students and staff are increasingly expanding the learning and social environment in higher education. It also questions the legal and moral responsibilities of universities to make all their online activities accessible to all students, regardless of disability.